Evaluation of hardness and color stability in the soft lining materials after thermocycling and chemical polishing. - Goiato, Marcelo Coelho [UNESP]; Falcón-Antenucci, Rosse Mary; Santos, Daniela Micheline dos [UNESP]; Pellizzer, Eduardo Piza [UNESP] (My University, 2009)
The aim of this study was to evaluate the Shore A hardness and color stability of two soft lining materials after thermocycling and when chemical polishing was used or omitted. Two acrylic-based soft lining materials were tested: Coe-Soft and Soft Confort, 14 specimens were made for each material. They were distributed in four groups according to the treatment performed. The specimens were thermocycled (1000 cycles) and half of the group submitted to chemical polishing (methyl methacrylate). Shore A hardness was determined and color stability was calculated by means of Commission International de l'Eclairage Lab uniform color scale using a spectrophotometer, the measurements were made immediately after deflasked, chemical polishing and thermocycling. Analysis of variance (ANOVA) and Tukey's tests were performed at p < 0.01. Color changes (deltaE) were observed after thermocycling in both soft lining materials: Soft Confort (10.60) showed significantly higher values than Coe-Soft (4.57). Coe-Soft (26.42) showed higher Shore A hardness values than Soft Confort (19.42). Chemical polishing did not influence in the color stability of both materials; however, influenced in the hardness values of Coe-Soft.
Keywords: Coe Soft denture lining material; Coe-Soft denture lining material; methacrylic acid derivative; color; dental care; denture; hardness; heat; tooth brushing; Color; Dental Polishing; Dental Stress Analysis; Denture Liners; Hardness; Hot Temperature; Methacrylates